2000
DOI: 10.1525/aeq.2000.31.3.283
|View full text |Cite
|
Sign up to set email alerts
|

“Points Ain't Everything”: Emergent Goals and Average and Percent Understandings in the Play of Basketball among African American Students

Abstract: This study examines the shifting nature of the cultural practice of basketball as players move from middle school to high school play and related shifts in players' statistical evaluations linked to play. Thirty‐four middle and high school African American basketball players were observed and interviewed as they participated in the practice of basketball. Results show that the practice of basketball differs at these two levels of play corresponding to differences in mathematics linked to play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 15 publications
2
80
0
4
Order By: Relevance
“…2 (e.g., Lave & Wenger, 1991;Nasir, 2000) and on everyday situations (e.g., Inagaki & Hatano, 1989;Rogoff, 1990) has analyzed long-term learning in everyday situations and offers insights into how learning activities can and/or should be organized. From these studies, some features of successful learning can be identified.…”
Section: New Learning Goalsmentioning
confidence: 99%
“…2 (e.g., Lave & Wenger, 1991;Nasir, 2000) and on everyday situations (e.g., Inagaki & Hatano, 1989;Rogoff, 1990) has analyzed long-term learning in everyday situations and offers insights into how learning activities can and/or should be organized. From these studies, some features of successful learning can be identified.…”
Section: New Learning Goalsmentioning
confidence: 99%
“…[13][14][15] These are two practices which are familiar to African American communities, atlarge but may not have been experienced by everyone. In Mahiri's [13] ethnographic investigation of the relationship between discourse features of African American male youth and basketball, Mahiri points to the role that basketball plays in providing young boys an opportunity to engage in analytical thinking activities.…”
Section: Strong Analytical Skillsmentioning
confidence: 99%
“…basketball, dominoes, card playing) in the lived experiences of Black boys and their ability to translate skills between formal education and informal contexts. In her study investigating thirty-four middle school Black student athletes transition from middle to high school, Nasir [14] found that students exhibit ability for higher level mathematical thinking skills and ability to set evaluation goals as the structure basketball practice changes during their transition from middle to high-school. Nasir considers these mathematical thinking skills 'practice-linked statistical concepts.'…”
Section: Strong Analytical Skillsmentioning
confidence: 99%
See 2 more Smart Citations